Dana Analisis Dampak Kebijakan Keuangan Pemerintah terhadap Pihak Ketiga Bank Swasta - Wijono, Setiawan; Mardanugraha, Eugenia (UI Scholars Hub, 2019)
The ability of Indonesia’s private banks to muster funds vary from one province to another. The test result from 33 provinces in Indonesia during 2011-2015 show that the ratio of GDP against BUDGETS, the private bank’s delivery channel ratio, and population density have a significant influence on the market share of private banks. When exclude DKI, the ratio of trade and services sector in regional GDP to bank deposits and the ratio of civil servants to the working population also have a significant effect. The ratio of APBD to GRDP gives a negative influence, while other variables contribute positively. Zoning policy forcing private banks to expand also networks in zone 5 and zone 6 which have not been great its potential. To provide incentives to private banks, the government need relaxes a few rules related to the exclusivity of state-owned banks. On the other hand private banks can focus on other variables that contribute positively to obtain optimal performance. Keywords: APBD, Regional GDP, private bank, BI zonation, OJK